Self-Governance as Agency in Post-Disaster Recovery - Oloruntoba, Richard; Asare-Doku, Winifred; Oloruntoba, Oluseye (Routledge, 2025)
The adverse impacts of natural and human-made disasters are reducible and avoidable, and communities can more readily recover from the impacts of both. While there are diverse strategies and mechanisms for recovery and rebuilding after disaster, the emphasis has been on national and local governments, and non-governmental organizations (NGOs) to act as agencies and instigators of recovery. As a result, there has been a limited focus on internal human agency and resources available for disaster recovery such as embodied in the concept of self-governance (Kooiman and Van Vliet, 2000). The capacity for actor-oriented self-governance is one major difference between people who successfully recover from disasters, and those who do not (Kooiman and Van Vliet, 2000). Self-governance is the ability of a person or group to function and lead themselves with little external influence (Kooiman and Van Vliet, 2000). At a collective level, how individuals and communities self-reorient, self-reorganize and use their resources and abilities to rebuild their lives and communities after a disaster is a critical factor in recovery. Research shows that individuals possess certain strengths and resources which they may not be aware of that can enhance their resilience and functioning (Kooiman and Van Vliet, 2000). This chapter discusses the concept of self-governance and positive psychology in the disaster recovery process and the relationship between positive psychology and self-governance approaches to recovery. The chapter first discusses the concept of self-governance and positive psychology. Second, it explores facilitators of self-governance in post-disaster recovery. Third, it discusses how self-awareness, psychological resilience and self-governance contribute to recovery after a disaster; and fourth, provides evidence-based approaches to utilizing these resources for post-disaster recovery.